2009
DOI: 10.1007/s10529-009-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tissue plasminogen activator production and specific growth rate in Chinese Hamster Ovary cells cultured in mannose at low temperature

Abstract: Chinese hamster ovary (CHO) cells, producing human recombinant tissue plasminogen activator (tPA), were grown with mannose (5, 20 and 40 mM) instead of glucose at 31, 33 and 37 degrees C. The highest tPA concentration (1.5 mg l(-1) at 144 h of cultivation) and tPA specific production rate (47 ng 10(-6) cell h(-1)) were obtained at 31 degrees C and 40 mM mannose. Regardless of the temperature or mannose concentration used, an inverse relationship between the specific growth rate and tPA specific production rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
5
14
3
Order By: Relevance
“…As shown in Table 1, regardless of the carbon source used, a decrease in the temperature of cultivation from 37 to 31ºC increased the culture longevity (defined as the time to reach 85% viability). Similar results have been previously reported for CHO cell cultures (Berrios et al 2009). In the CHO cultures with glucose, the qtPA increased when the cultivation temperature was decreased from 37 to 31ºC (Table 1), indicating that 31ºC was the most suitable condition for rh-tPA production.…”
Section: Cell Growth and Rh-tpa Production In Batch Culturessupporting
confidence: 92%
See 2 more Smart Citations
“…As shown in Table 1, regardless of the carbon source used, a decrease in the temperature of cultivation from 37 to 31ºC increased the culture longevity (defined as the time to reach 85% viability). Similar results have been previously reported for CHO cell cultures (Berrios et al 2009). In the CHO cultures with glucose, the qtPA increased when the cultivation temperature was decreased from 37 to 31ºC (Table 1), indicating that 31ºC was the most suitable condition for rh-tPA production.…”
Section: Cell Growth and Rh-tpa Production In Batch Culturessupporting
confidence: 92%
“…Thus, an increase in qtPA was observed when the temperature was decreased from 37 to 34ºC, whereas the lowest qtPA value was observed at 31ºC. In contrast, Berrios et al (2009) have reported that the qtPA value can be enhanced in batch cultures of CHO cells conducted at 31ºC, using mannose as the carbon source. Furthermore, Berrios et al (2011) reported that replacing glucose by mannose in continuous culture, increased specific productivity of t-PA at high concentrations of the Cell growth and rh-tPA production in semi-perfusion cultures Figure 1 shows the profile of cell growth, cell viability and rh-tPA concentration in semi-perfusion cultures of CHO cells cultured at 37ºC with glucose as the main carbon source (SPC1).…”
Section: Cell Growth and Rh-tpa Production In Batch Culturesmentioning
confidence: 92%
See 1 more Smart Citation
“…A number of approaches have been taken to improve the productivity of mammalian cell lines through cell line engineering, including the direct manipulation of productivity (Peng and Fussenegger, 2009;Tigges and Fussenegger, 2006) as well as the suppression of apoptosis (Arden et al, 2007;Ifandi and Al-Rubeai, 2005). An important approach to achieving this aim is via manipulation of the cell-specific growth rate, especially given substantial evidence that the growth rate and specific production rate of CHO are directly linked (Berrios et al, 2009;Lipscomb et al, 2005;Yokota and Tanji, 2008). A highly desirable feature for any production cell line is an ability to grow quickly in the bioreactor, shortening time spent in the log phase of growth.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, 2 approaches have important implications on the culture performance. Changing the culture temperature to a mild hypothermia (33 to 30 °C) has a positive effect on the productivity of a wide range of recombinant proteins [89,90,3] in batch culture. A reduced temperature can positively affect the cellular metabolism, which then has an impact on Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/6/15 11:59 AM the design of the feed medium in a fed-batch cultivation.…”
Section: Use Of Genetic and Environmental Manipulations On Fed-batch mentioning
confidence: 99%